FAKTOR KUALITAS SDM YANG MEMPENGARUHI KUALITAS PELAYANAN AKTA KELAHIRAN DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA PONTIANAK - Harmoko E.21111099 (FISIP Universitas Tanjungpura, 2013)
This study aims to determine the factors that influence the birth certificate of service with the study in the Office of Population and Civil Registration Pontianak . The method used in this study is a qualitative research method with a descriptive explanation regarding the birth certificate of service in the Office of Population and Civil Registration Pontianak . The results showed that the velocity in the birth certificate of service in the Office of Population and Civil Registration Pontianak is still lacking and does not meet the expectations of society . Speed ??in the service of the birth certificate in the Office of Population and Civil Registration Pontianak influenced by the birth certificate procedures are long and require a lot of the maintenance requirements of the neighborhood level to the Village . This is also why people become reluctant to take care of the birth certificate . Suggestions writer for the Population and Civil Registration Department Pontianak City is expected to continue to improve services birth certificate . This can be done by the Office of Population and Civil Registration Pontianak for example by continuing to improve the quality of employees and complete the infrastructure and physical facilities more adequate . The officer in the Office of Population and Civil Registration Pontianak is expected to continue to improve the quality of personal well by increasing competence by following a number of training and continue to be committed to provide optimum service to the community . Keywords : Birth Certificate Services, Physical Facilities Office, Human Resources